Improving Students’ Speaking Skill Through CLT An Action Research - Anggraini Anggraini (Wanastra: Jurnal Bahasa dan Sastra, 2018)
This is an action research study that aimed to improve students’ speaking skill through communicative language teaching technique. It discusses how  communicative language teaching technique can improve students’ speaking skill. Private language schools, on other hand, tend to be better equipped than some goverment schools(thought his not always the case), at English training course students’ speaking skill is still low especially in basic level.The students of english training course find the diffilculties in speaking skill; the students have felt boring with the old techinque. Especially in improving their speaking skill.In the class room action research the writer uses  the picture reconstruction, and students have to discuss and tell in their group, each group contain of 4 until 5 students, the writer made three cycles, and the writer gives the score each cycle according to the speaking measurement.Based on the result research and concluded that the students can improve their speaking skill through communicative language teaching technique. In the first cycle the average students’ score is 60, in the second is 70 point, and in the last cycle is 80 point, and writer has made a graphic of each cycle.Keys word: Improving, speaking, communicative language teaching technique .